Comparison of the performance levels of US female professional golf players - Kim, E.-K.; Chae, J..-S. (International Journal of Applied Sports Sciences, 2021)
This study assessed the relative contribution of technical variables affecting birdies (Bir) and official money (OM) among the top 10 players of the Ladies Professional Golf Association. The average difference in performance variables was assessed according to prize money, country and continent, and time. Multiple regression analysis and one-way ANOVA were conducted, and a p-level less than .05 was considered statistically significant. First, putting average (PA) made the largest relative contribution to Bir and OM, followed by green in regulation (GIR). Second, players with highest prize-money earnings had significantly better drive distance (DD), drive accuracy (DA), sand saves (SS), and PA than median/lowest prize-money earners. Moreover, GIR was found to be accurate in distinguishing players` prize-money rankings. Third, Korean and Oceanian golfers had significantly better PA than American and European golfers; Korean golfers demonstrated better Bir, Par3, Par4, and Par5 than players from other countries and continents. Lastly, women golfers` performance improved in a 10-year-cycle. Particularly, DD, DA, and GIR significantly improved over each cycle, and Bir, Par3, Par4, and Par5, but not Eag, also significantly improved.